Karakteristik chiffon berbahan baku tepung pisang lewat matang - Tjahja Muhandri; Sutrisno Koswara; Aminullah Aminullah (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Background: The X’s bakery industry makes banana chiffon using fresh banana fruit as a raw material; however, fresh bananas were prone to rot. Research purposes: to apply overripe banana flour in making chiffon and study the characteristic differences with fresh banana chiffon. Method: This research consisted of making overripe banana flour using foam mat drying and making banana chiffon. The chiffon cake was made by adding 20g, 40g, and 60g banana flour (150g flour base) and control of 50g fresh ripe bananas. The yield, color, repose angle, and moisture content of overripe banana flour were analyzed, including specific volume, chiffon color, chiffon swelling, texture profile, and moisture content in chiffon cake. A complete one-factor random design with Dunnet’s analysis was used. Results and Discussion: The results showed that overripe banana flour has yellowish color with a yield of 26.23±0.45%, a repose angle of 27.44±0.92, and a moisture content of 7.97±0.43% (wet base). Statistical analysis showed that chiffon of overripe banana flour did not differ significantly at 5% from than chiffon of fresh bananas on several parameters. They were the specific volume of the dough and moisture content and swelling, hardness, adhesiveness, elasticity, and chewing power. In addition, the chiffon’s crumb section of banana flour has a lower brightness compared to fresh banana chiffon, where the top, middle, and side crusts were not significantly different. Conclusion: These results indicated that the use of banana flour could replace fresh bananas in chiffon cake.